The Hegemony Of White Commodity Culture Toward Afro-American: An Analysis Of Susan Willis' I Shop Therefore I Am - Astuti, Irma Windy (English Education Department, Universitas Islam Indonesia, 2012)
This paper is meant to analyze Willis' work which underlines the influence of commodity culture of mainstream white society in America towards other race, particularly Afro-American as one of the country's minority races in the 1980's. The work further posits that the white America's popular and mass culture has ingrained and legitimately shaped the way Afro-American see and value their own culture and self identity, and that its spread and control is both political and materialistic. This paper is seek to put forward that Willis' idea can be visibly viewed through and associated with Gramsci's theory of hegemony in understanding the underlying agenda advocated by the more superior group (white) towards their subordinate counterparts (Afro-American).Key words: white mass culture, afro-American, hegemony